2021
DOI: 10.1002/aoc.6377
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and molecular dynamics simulation study on the delivery of some common drugs by ZIF‐67, ZIF‐90, and ZIF‐8 zeolitic imidazolate frameworks

Abstract: Anti‐seizures have been frequently used for a long time. Most of these antiepileptic drugs, which are used on a daily basis, are central nervous system depressants, and their excessive use damages the respiratory system. Therefore, in order to achieve the desired therapeutic goals, avoiding side effects and drug interactions, it is very important to use targeted medications. Among the metal–organic frameworks (MOFs), ZIF nanoparticles have several advantages such as smooth capillary flow and the slow release o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 55 publications
0
14
0
1
Order By: Relevance
“…Computational studies can be helpful to assess the MOF’s potential for e.g. drug delivery without extensive experiments. In this study, MUT-2, a new NO 2 -functionalized 3D IMOF with helical channels, is reported. Its potential for drug loading was evaluated computationally.…”
Section: Introductionmentioning
confidence: 99%
“…Computational studies can be helpful to assess the MOF’s potential for e.g. drug delivery without extensive experiments. In this study, MUT-2, a new NO 2 -functionalized 3D IMOF with helical channels, is reported. Its potential for drug loading was evaluated computationally.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristic peak of N 1s appeared at 398.3 eV (Figure 5B-c), proving the existence of the N−Zn bond. 36 The characteristic peak at 286.1 eV corresponding to C 1s indicated the presence of a C−N bond in the ligand 2-Mim of ZIF-8 (Figure 5B-b). The characteristic peak of S in Figure 5A-b could be due to the sulfonic acid groups in AMPS and disulfide bonds in BAC.…”
Section: Characterization Of Zeta Potentialmentioning
confidence: 97%
“…In silico, many factors that contribute to loading capacity, release behaviour and drug–MOF interactions can be studied effectively [ 210 ]. The development of computational techniques can dramatically shorten the time needed for experimental investigations—for example, drug loading simulations predicted ZIF-8 to have the highest loading capacities compared to ZIF-90 and ZIF-67 [ 211 ], allowing to bypass the time taken to optimise by trial-and-error method, and hence rapidly minimise the time and resources needed to perform MOF loading studies. The synergy between computational and experimental studies in the field of drug delivery using MOFs can provide us with greater insight into interactions between drugs and host materials for optimised delivery.…”
Section: Use Of Computational Modelling In Drug Delivery Studies Usin...mentioning
confidence: 99%